2016
DOI: 10.1016/j.proeng.2016.06.263
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Cap-mounted Tri-axial Accelerometer for Measurement of Distance, Lap Times and Stroke Rates in Swim Training

Abstract: This paper will report some of the findings from a trial which recorded accelerometer data from six elite level swimmers (three female and three male, varying primary event stroke and distance) over the course of a regular 15 week training block. Measurements from a head-mounted accelerometer are used to determine when the athlete is swimming, marking of turning points (and therefore distance and lap-time measurements), and is processed by frequency analysis to determine stroke-rate. Comparison with video wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…[ 17 , 22 ] proposed a threshold-based methodology from a combination of orientation and component energy to determine the stroke type with 96.1% accuracy. This method, sometimes combined with a gyroscopic signal, has been widely used in the literature for stroke recognition [ 23 , 24 , 25 ]; as well as for the wall push, turn, and touch identification sometimes used for lap time (LT) calculation [ 19 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. LT calculation refers to identified peaks in the acceleration signal.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 , 22 ] proposed a threshold-based methodology from a combination of orientation and component energy to determine the stroke type with 96.1% accuracy. This method, sometimes combined with a gyroscopic signal, has been widely used in the literature for stroke recognition [ 23 , 24 , 25 ]; as well as for the wall push, turn, and touch identification sometimes used for lap time (LT) calculation [ 19 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. LT calculation refers to identified peaks in the acceleration signal.…”
Section: Introductionmentioning
confidence: 99%
“…For validation, in addition to inertial sensors, they attached a video camera for tagging the activities. Regarding the sports activity, as well as the previous example, we observed that multiple solutions have been proposed to assist users in performing activities such as swimming [52], hokey [53], golf [57], or motorcycle VR [58]. Such a system was proposed by Michaels et al [52] in order to coach new users to use inertial sensors.…”
Section: Head Motion Systemsmentioning
confidence: 92%
“…Regarding the sports activity, as well as the previous example, we observed that multiple solutions have been proposed to assist users in performing activities such as swimming [52], hokey [53], golf [57], or motorcycle VR [58]. Such a system was proposed by Michaels et al [52] in order to coach new users to use inertial sensors. Their system used only a tri-axial accelerometer and considered the following requirements: to be lightweight, waterproof, have a long life battery, and to save acquired data for a long period.…”
Section: Head Motion Systemsmentioning
confidence: 92%
See 2 more Smart Citations